Simulación de áreas de alta consecuencia para gasoductos - Díaz-Parra, Orlando; Vera-López, Enrique (Revista Científica, 2018)
The gas pipeline is used for the transport of natural gas at a great distance. Risks derived from the handling of a combustible material transported under high pressure, by pipelines that pass close to where people live, makes it necessary to adopt prevention, mitigation and control measures to reduce the effect in case of ignition of a gas leak. This work shows the development of a new mathematical model to determine areas of high consequence and their application, using widely available and easy to use software, such as Google Earth and Excel, to determine and visualize the area up to which the level of radiation can affect the integrity of people and buildings. The model takes into account the pressure drop into the gas pipeline from the compression station, the gas leakage rate and possible forms of gas ignition. This development is an alternative to the use of specialized software and highly trained personnel. The simulation is applied to a traced of the Miraflores-Tunja gas pipeline, using a macro developed in Excel to determine the impact area and compare it with the coordinates of the vulnerable areas. The zones where these areas intersect are constituted in high consequence areas and are identified along with the sections of the pipeline that affect them, to provide the operator with a risk analysis tool for the determination and visualization of the gas pipeline and its environment.